1995
DOI: 10.1111/j.1460-9568.1995.tb01158.x
|View full text |Cite
|
Sign up to set email alerts
|

NMDA and Kainate Induce Internucleosomal DNA Cleavage Associated With Both Apoptotic and Necrotic Cell Death in the Neonatal Rat Brain

Abstract: Injection of N-methyl-D-aspartate (NMDA) or kainate in the striatum of 7-day-old rats induced massive cell loss in the ipsilateral striatum, hippocampus and inner cortical layers. In order to examine whether apoptosis contributes to cell death in this model of excitotoxic injury we examined the progression of internucleosomal DNA fragmentation and changes in cellular ultrastructure. Agarose gel electrophoresis of DNA extracted from the ipsilateral striatum, cerebral cortex and hippocampus clearly showed breakd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
2

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(51 citation statements)
references
References 49 publications
3
45
1
2
Order By: Relevance
“…Thus, both necrotic and apoptotic cell death may coexist in the same cell population (Bonfoco et al, 1995;van Lookeren Campagne et al, 1995). This seems to be the case for the neuronal damage induced by gp120 under our experimental conditions.…”
Section: Both Apoptosis and Necrosis Are Responsible For Gp120-inducementioning
confidence: 73%
See 1 more Smart Citation
“…Thus, both necrotic and apoptotic cell death may coexist in the same cell population (Bonfoco et al, 1995;van Lookeren Campagne et al, 1995). This seems to be the case for the neuronal damage induced by gp120 under our experimental conditions.…”
Section: Both Apoptosis and Necrosis Are Responsible For Gp120-inducementioning
confidence: 73%
“…NMDA-induced neurotoxicity usually has been associated with necrosis (Meldrum and Garthwaite, 1990). However, a growing corpus of data has shown that both apoptosis and necrosis can be involved in excitotoxicity (Bonfoco et al, 1995;van Lookeren et al, 1995). In particular, a study on cortical neurons showed that mild or intense NMDA stimuli can result in predominantly apoptotic or necrotic neuronal damage, respectively (Bonfoco et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…21 Conversely, in necrosis, activation of endonucleases may be a non-specific event occurring in parallel with many other destructive processes, so that DNA laddering appears only evanescently en route to gross cell failure. 9,16,23,51 In summary, the weight of evidence obtained here suggests that even slowly triggered excitotoxic death in neocortical cell cultures occurs primarily by necrosis. This conclusion complements our earlier study indicating that rapidly triggered NMDA receptor-mediated excitotoxic death in the same system also occurs by necrosis.…”
Section: 20mentioning
confidence: 99%
“…1 Some neurons degenerating after intraparenchymal injection of excitotoxins exhibit chromatin condensation and internucleosomal DNA fragmentation. 43,51 Furthermore, evidence has also accumulated that hypoxic-ischemic neuronal death may have an apoptosis component. Internucleosomal DNA fragmentation has been demonstrated in degenerating neurons after ischemic insults, 22,33,40,49 and inhibitors of macromolecule synthesis attenuated neuronal death in certain animal models of ischemia.…”
mentioning
confidence: 99%
“…Kure et al [12] showed that cortical neurons treated with glutamate revealed internucleosomal DNA fragmentation (DNA ladders) and actinomycin D-sensitive neuronal death. NMDA or kainate produced chromatin condensation and DNA ladders in cortical and cerebellar neurons [2,15,17], suggesting that excitotoxicity can induce apoptosis as well as necrosis. In as much as caution that DNA ladders and chromatin condensation may not differentiate apoptosis and necrosis [7], we set out experiments to determine patterns of glutamate neurotoxicity in neuron-rich cortical cell cultures by analyzing ultrastructural change in cytoplasm and nucleus, DNA fragmentation, and chromatin condensation (see abstract, [16]).…”
mentioning
confidence: 99%